2017
DOI: 10.1177/1071100717732762
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Simultaneous Stretching of the Achilles Tendon and Plantar Fascia in Individuals With Plantar Fasciitis

Abstract: II, lesser quality RCT or prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
1
23
0
4
Order By: Relevance
“…All the above studies demonstrate that the MG experiences greater mechanical loading during daily activities. Clinically, most studies have reported that reduced muscle stiffness can alleviate the symptoms of patients with PF 2,6,9,21 . For example, chronic symptoms lasting longer than 4 months might cause the tissue to be stiffer and to become more difficult to stretch 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the above studies demonstrate that the MG experiences greater mechanical loading during daily activities. Clinically, most studies have reported that reduced muscle stiffness can alleviate the symptoms of patients with PF 2,6,9,21 . For example, chronic symptoms lasting longer than 4 months might cause the tissue to be stiffer and to become more difficult to stretch 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, chronic symptoms lasting longer than 4 months might cause the tissue to be stiffer and to become more difficult to stretch 2 . Stretching of the gastrocnemius-AT complex is widely considered to be an effective treatment for PF and reducing foot and ankle pain because stretching addresses PF caused by tight gastrocnemius and intrinsic foot muscles 2,6,9 . After eccentric training, the fascicle length of the MG increased 12%, but this change was not observed for the LG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, an anatomical connection between the Achilles tendon and the plantar fascia makes the relationships among the plantar fascia, calcaneus, and Achilles tendon biomechanically complex, so we assumed this structure may transfer stress from one side of calcaneus to another. Some studies also found that Achilles tendinopathy and heel pain can collectively benefit from similar conservative and surgical treatments by reducing the tension on both sides, such as eccentric calf stretching and gastrocnemius recession [2,23,24]. erefore, the Achilles tendon, calcaneus, and plantar fascia should be considered as a whole e Fowler-Philip angle was measured between an inferior line which was tangent to the inferior margin of the calcaneocuboid joint and the plantar tuberosity of the calcaneus and a superior line which was tangent to the posterior prominence at the insertion of the Achilles tendon.…”
Section: Discussionmentioning
confidence: 99%